Introduction to laser spectroscopy - Abramczyk, Halina (Elsevier, 2005)
This book is intended to be used by students of chemistry, chemical engineering, biophysics, biology, materials science, electrical, mechanical, and other engineering fields, and physics. It assumes that the reader has some familiarity with the basic concepts of molecular spectroscopy and quantum theory, e.g., the concept of the uncertainty principle, quantized energy levels, but starts with the most basic concepts of laser physics and develops the advanced topics of modern laser spectroscopy including femtochemistry. The major distinction between this book and the many fine books available on laser physics and time resolved spectroscopy is its emphasis on a general approach that does not focus mainly on an extensive consideration of time resolved spectroscopy. Books at the correct level of presentation for beginners tend to be focused either totally or mainly on the basic fundamentals of lasers and include only a minimal amount of material on modern ultrashort laser spectroscopy and its chemical, physical and biological applications. On the other hand, books that contain the desired material to a significant degree, are too advanced, requiring too much prior knowledge of nonlinear optics, quantum theory, generation of ultrafast pulses, detection methods, and vibrational and electronic dynamics. This book is intended to fill the gap. More advanced problems of modern ultrafast spectroscopy are developed in the later chapters using concepts and methods from earlier chapters [...].
Keywords: spektroskopia laserowa; lasery; nonlinear optics; lasers in medicine; laser spectroscopy; lasers; optyka nieliniowa; lasery w medycynie